2004
DOI: 10.1254/jphs.fp0040024
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Inhibition of the Slowly Activating Delayed Rectifier K+ Current in Guinea Pig Ventricular Cells

Abstract: Abstract. Single ventricular cells were enzymatically isolated from guinea pig hearts and the effects of sevoflurane on the delayed rectifier K + current were investigated by the patch clamp method. The rapidly (I Kr ) and slowly activating delayed rectifier K + current (I Ks ) were isolated using chromanol 293B, a selective blocker for I Ks , a blocker for I Kr . Sevoflurane and halothane decreased I Ks in a concentration-dependent manner with an IC 50 value of 0.38 mM for sevoflurane and 1.05 mM for halotha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 39 publications
(43 reference statements)
1
16
1
Order By: Relevance
“…These differential effects of propofol on I Kr and I Ks are qualitatively similar to those of sevoflurane (Heath and Terrar, 1996;Kang et al, 2006, Kojima et al, 2015Shibata et al, 2004). Previous studies have demonstrated that propofol concomitantly blocks other ionic currents, especially L type Ca 2+ current (I Ca,L ) in ventricular myocytes (Yang et al, 1996), which results in minimal or no effect on ventricular action potential duration and QTc interval in experimental and clinical settings (Kojima et al, 2015;Puttick and Terrar, 1992;Staikou et al, 2014).…”
supporting
confidence: 56%
“…These differential effects of propofol on I Kr and I Ks are qualitatively similar to those of sevoflurane (Heath and Terrar, 1996;Kang et al, 2006, Kojima et al, 2015Shibata et al, 2004). Previous studies have demonstrated that propofol concomitantly blocks other ionic currents, especially L type Ca 2+ current (I Ca,L ) in ventricular myocytes (Yang et al, 1996), which results in minimal or no effect on ventricular action potential duration and QTc interval in experimental and clinical settings (Kojima et al, 2015;Puttick and Terrar, 1992;Staikou et al, 2014).…”
supporting
confidence: 56%
“…[2][3][4]7) Furthermore, the pre-treatment with chromanol 293B markedly potentiated the QT-interval prolonging effect of d-sotalol in the present model, which is in good accordance with the previous studies using the in vitro canine and human ventricular tissues. 4,5) Previous electrophysiological studies have demonstrated that anesthetic concentration of halothane inhibits multifarious K ϩ currents including the I Kr , I Ks , transient outward current (I to ) and inward rectifier current (I K1 ) in the isolated cardiomyocytes, [11][12][13][14] whereas such modulatory effects of urethane-anesthesia on various ionic channels have not been reported. So, these electrophysiological effects of halothane could reduce the repolarization reserve of the guinea-pig heart, which might have unmasked the I Ks blocker-induced QT-interval prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is sevoflurane, which inhibits hERG current in Xenopus oocytes in a concentration-dependent manner (10-27% inhibition at 0.14-0.65 mmol/L) and prolongs the QTc interval in guinea pigs dose-dependently (Yamada et al, 2006). This hERG-blocking potential of sevoflurane, however, was not confirmed by other groups, who detected hardly an effect of sevoflurane (0.65 mmol/L) on isolated I Kr in guinea pig ventricular myocytes (Shibata et al, 2004) or an only marginal inhibition of hERG current at supratherapeutic concentrations (-17% at 3 mmol/L; Kang et al, 2006). Instead of an I Kr or hERG block, these two groups demonstrated an I Ks block by sevoflurane (IC 50 0.38 mmol/L) and halothane (IC 50 1.07 mmol/L) in guinea pig ventricular myocytes (Shibata et al, 2004) and in KvLQT1-minK expressing Chinese hamster ovary (CHO) cells (sevoflurane IC 50 1.3 mmol/L; Kang et al, 2006).…”
Section: Cardiac Delayed Rectifier Potassium Channels I Kr and I Ksmentioning
confidence: 84%